Kombinasi Pembobotan PIPRECIA-S dan Metode SAW dalam Pemilihan Ketua Organisasi Sekolah - Setiawansyah Setiawansyah; Very Hendra Saputra (PT. SNN MEDIA TECH PRESS, 2023)
This study aims to select the head of the school organization using the SAW method and PIPRECIA-S weighting, so that the assessment results in the weighting of criteria are more objective based on calculations from the PIPRECIA-S weighting method. The results of the election of the head of the school organization using the SAW method and the weighting of PIPRECIA-S recommended Jamaludin as a candidate for the head of the school organization because the final results of the ranking got Rank 1 with a total score of 1,821. Rank 2 was obtained by Bustomi with a final score of 1,763, rank 3 was obtained by Budiman with a final value of 1,698. The test results based on filling out questionnaires from each category 73% strongly agree, 25% agree, 2% are sufficient, and 0% disagree, so that they can be used in determining candidates for organizational chairman.